Penambahan Tepung Biji Nangka Dalam Pembuatan Bolu Kukus Buah Nangka - Fitriani, Dewi; Azhar Firdaus, Friska (JURNAL PARIWISATA VOKASI, 2024)
This research aims to determine the differences in taste the taste of jackfruit steamed sponge cake using jackfruit seed flour, knowing the nutritional content produced in jackfruit steamed sponge cake using jackfruit seed flour and knowing the detailed comparison of production costs between jackfruit steamed sponge cake using jackfruit seed flour and the comparison. The data collection technique used is by product experimentation, distributing questionnaires, observation. Meanwhile, the data analysis technique uses a Likert scale. The author makes conclusions regarding the addition of jackfruit seed flour in making steamed jackfruit cake as follows: Taste of steamed jackfruit seed cake. Comparison with experimental jackfruit seed cake according to trained and untrained authors. Suggestions given for solving the problem are necessary: ​​1. Promotion regarding the use of additional ingredients using jackfruit seed flour as a local food ingredient to make steamed cakes 2. Utilization of jackfruit seed flour to be used as an alternative food ingredient to replace wheat flour, thereby reducing imports